1997
DOI: 10.1074/jbc.272.10.6479
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Adenovirus with Polycationic Polymers and Cationic Lipids Increase the Efficiency of Gene Transfer in Vitro and in Vivo

Abstract: We have investigated the lignin peroxidase-catalyzed oxidation of guaiacol and the role of veratryl alcohol in this reaction by steady-state and pre-steady-state methods. Pre-steady-state kinetic analyses demonstrated that guaiacol is a good substrate for both compounds I and II, the two-and one-electron oxidized enzyme intermediates, respectively, of lignin peroxidase. The rate constant for the reaction with compound I is 1.2 ؋ 10 6 M ؊1 s ؊1. The reaction of guaiacol with compound II exhibits a K d of 64 M a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
218
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(232 citation statements)
references
References 50 publications
11
218
3
Order By: Relevance
“…In comparison, adenoviruses which carry a net negative charge, are less likely to do so. This may be of relevance to a recent series of experiments 29,30 in which adenoviruses combined with polycations, were shown to mediate improved gene transfer in both primary cell cultures and in mouse models. Given our data and that mice are likely to produce smaller quantities of mucus, application of polycation complexed adenoviruses to larger animal models may not prove as successful.…”
Section: Discussionmentioning
confidence: 71%
“…In comparison, adenoviruses which carry a net negative charge, are less likely to do so. This may be of relevance to a recent series of experiments 29,30 in which adenoviruses combined with polycations, were shown to mediate improved gene transfer in both primary cell cultures and in mouse models. Given our data and that mice are likely to produce smaller quantities of mucus, application of polycation complexed adenoviruses to larger animal models may not prove as successful.…”
Section: Discussionmentioning
confidence: 71%
“…[6][7][8] One strategy for obtaining CAR-independent entry in Ad5-resistant cells is to make noncovalent complexes of adenovirus (Ad) with cationic agents. [9][10][11][12][13][14][15][16] The cationic components can associate with the Ad particles due to the net negative viral surface charge, and hence, the attachment to the negatively charged cell membrane is facilitated. This method enables potent gene delivery via CAR-independent cell infection, demonstrating that the interaction with the primary receptor is not crucial for cellular entry.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] This concept has been exemplified in studies which demonstrate that purified quantities of fiber can inhibit viral attachment to cell surfaces 28 and that attachment can also be inhibited by anti-fiber antibodies. 29 Viruses used in all of the previously described trials are respiratory viruses with fiber proteins that are specific for receptors located on epithelia of the lung and other respiratory tissues. 30 This specificity was emphasized in the HBsAg study conducted by Chengalvala et al 24 They found that delivery of the viral vector via intratrachial administration provided adequate immunity to HBsAg while, as mentioned previously, oral administration did not.…”
Section: Introductionmentioning
confidence: 99%